Acampe Rigida (Buch. - Ham. Ex J.E. Smith) P.F. Hunt (orchidaceae): A New Record for Darjeeling Himalaya of West Bengal, India - Lama, Rajendra Yonzoned; Bhujel, R. B.; Rai, Samuel (Indian Forester, 2014)
No Abstract